Maternal and perinatal factors affecting vitamin D status of very low birth weight infants hospitalized in neonatal intensive care unit - Wibowo, Tunjung; Anggraini, Alifah; Safrida, Elysa Nur; Wandita, Setya; Haksari, Ekawaty Lutfia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2024)
Background: Vitamin D deficiency is a global problem in premature infants. Vitamin D deficiency is associated with skeletal and non-skeletal disease. In premature infants, vitamin D deficiency is primarily associated with metabolic bone disease. Objective: The study aims to investigate the prevalence and risk factors of vitamin D deficiency in very low birth weight (VLBW) infants who were hospitalized in the neonatal intensive care unit (NICU) of a tertiary hospital in a developing country. Methods: A retrospective cohort was conducted at the NICU of Dr. Sardjito General Hospital, Yogyakarta. VLBW infants (inborn and outborn), hospitalized between January 1, 2018, and December 31, 2020, were enrolled in this study. Data on maternal (age (years), parity, education level, and socio-economic status) and neonatal (birth weight, birth length, and head circumference), gestational age, age of serum 25 hydroxy-vitamin D (25-OHD), sex, type of feeding, postnatal steroid) was taken from the medical records. Serum 25-OHD measurement was conducted at the age of around 4 weeks. Throughout the first 24 hours following birth, all infants at Dr. Sardjito General Hospital weighing <1,500g would receive total parenteral nutrition (TPN). For infants who were referred to Sardjito General Hospital, nutritional and feeding history including TPN was assessed through anamnesis from the nurses or midwives who transport the patient and from referral records. Results: A total of 165 very low birth weight infants consisting of 88 male and 77 female newborns were included in this study. The mean ± SD of the vitamin D level was 11.5 ± 7.6 ng/ml (range 2.9 - 45.5 ng/ml). The prevalence of Vitamin D insufficiency, deficiency, and severe deficiency were 12.1; 55.2; and 23%; respectively. Receiving TPN was positively and independently associated with vitamin D levels (p=0.006). Conclusions: There is a positive relationship between the administration of TPN and serum 25-OHD level in VLBW infants hospitalized in the NICU.